The role of ncRNAs and exosomes in the development and progression of endometrial cancer - Niebora, Julia; Woźniak, Sławomir; Domagała, Dominika; Data, Krzysztof; Farzaneh, Maryam; Zehtabi, Mojtaba; Dari, Mahrokh Abouali Gale; Pour, Fatemeh Khojasteh; Bryja, Artur; Kulus, Magdalena; Mozdziak, Paul; Dzięgiel, Piotr; et al. (Frontiers in Oncology, 2024)
Endometrial cancer (EC) is the one of the most common gynecologic cancers. In recent years, research has focused on the genetic characteristics of the tumors to detail their prognosis and tailor therapy. In the case of EC, genetic mutations have been shown to underlie their formation. It is very important to know the mechanisms of EC formation related to mutations induced by estrogen, among other things. Non-coding RNAs (ncRNAs), composed of nucleotide transcripts with very low protein-coding capacity, are proving to be important. Their expression patterns in many malignancies can inhibit tumor formation and progression. MicroRNAs (miRNAs), several varieties of which are associated with normal endometrium, as well as its tumor, also play a particularly important role in gene expression. MiRNAs and long non-coding RNAs (lncRNAs) affect many pathways in EC tissues and play important roles in cancer development, invasion and metastasis, as well as resistance to anticancer drugs through mechanisms such as suppression of apoptosis and progression of cancer stem cells. It is also worth noting that miRNAs are highly precise, sensitive and robust, making them potential markers for diagnosing gynecologic cancers and their progression. Unfortunately, as the incidence of EC increases, treatment becomes challenging and is limited to invasive tools. The prospect of using microRNAs as potential candidates for diagnostic and therapeutic use in EC seems promising. Exosomes are extracellular vesicles that are released from many types of cells, including cancer cells. They contain proteins, DNA and various types of RNA, such as miRNAs. The non-coding RNA components of exosomes vary widely, depending on the physiology of the tumor tissue and the cells from which they originate. Exosomes contain both DNA and RNA and have communication functions between cells. Exosomal miRNAs mediate communication between EC cells, tumor-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs) play a key role in tumor cell proliferation and tumor microenvironment formation. During the synthesis of exosomes, various factors such as genetic and proteomic data are upregulated. Thus, they are considered an interesting therapeutic target for the diagnosis and prognosis of endometrial cancer by analyzing biomarkers contained in exosomes.